Architectural Contextualization of Heritage Museum Artifacts Using Augmented Reality - Eslam Nofal (Studies in Digital Heritage, 2018)
Context is crucial for understanding meanings and values of heritage. Several heritage artifacts from recently destroyed monuments are exhibited in different museums around the world. As such contextualizing those isolated heritage artifacts enables museums to communicate architectural and spatial qualities of the original context to their visitors. With the rapid evolution of digital technologies, museums started to incorporate Augmented Reality (AR) to present and interpret their collections in more appealing and exciting ways. AR allows both an enrichment of heritage communication, and also encouragement of interactivity in museums. Through a field study in a real-world museum environment, we investigated how AR enhances the communication of the original context of an isolated artifact from the Nimrud palace in Iraq. We deployed a mixed-method evaluation methodology that led to an effective and engaging communication of the architectural context of that artifact, particularly perceiving and recalling architectural features and spatial dimensions. We conclude the paper with a set of discussion points about how AR positively affects visitors’ memorability of architectural qualities, and how it provokes their curiosity to explore more information. We highlight some considerations about AR visualization, such as how levels of embellishment direct user’s focus of attention, and which aspects should be considered when using AR abstract visualization to communicate heritage. We outline several design recommendations to overcome current AR usability issues in museums about intuition, freedom of movement, and age-related differences.